The Effect of Artichoke Leaf Extract on Alanine Aminotransferase and Aspartate Aminotransferase in the Patients with Nonalcoholic Steatohepatitis - Vajiheh Rangboo; Mostafa Noroozi; Roza Zavoshy; Seyed Amirmansoor Rezadoost; Asghar Mohammadpoorasl (International Journal of Hepatology)
Background. Based on recent basic and clinical investigations, the extract of artichoke (Cynara scolymus) leaf has been revealed to be used for hepatoprotective and cholesterol reducing purposes. We aimed to assess the therapeutic effects of artichoke on biochemical and liver biomarkers in patients with nonalcoholic steatohepatitis (NASH). Methods. In a randomized double blind clinical trial, 60 consecutive patients suffering NASH were randomly assigned to receive Cynara scolymus extract (as 6 tablets per day consisting of 2700 mg extract of the herb) as the intervention group or placebo as the control group for two months. Results. Comparing changes in study markers following interventions showed improvement in liver enzymes. The levels of triglycerides and cholesterol were significantly reduced in the group treated with Cynara scolymus when compared to placebo group. To compare the role of Cynara scolymus use with placebo in changes in study parameters, multivariate linear regression models were employed indicating higher improvement in liver enzymes and also lipid profile particularly triglycerides and total cholesterol following administration of Cynara scolymus in comparison with placebo use. Conclusion. This study sheds light on the potential hepatoprotective activity and hypolipidemic effect of Cynara scolymus in management of NASH. This clinical trial is registered in the IRCT, Iranian Registry of Clinical Trials, by number IRCT2014070218321N1.